Dipeptidyl peptidase‐4 inhibitor‐associated cutaneous eruptions: a retrospective observational study. (1st July 2022) - Duraisamy, Prasanna; Jagadeesan, Soumya; Eapen, Malini; Thomas, Jacob
Summary: Background: Dipeptidyl peptidase (DPP)‐4 plays a complex role in immune regulation and its inhibition can have effects on the pathogenesis of various skin diseases. Studies have shown that DPP‐4 inhibitors are associated with an increased risk of bullous pemphigoid (BP). Aim: To analyse the clinical and histopathological features of cutaneous adverse events in patients on DPP‐4 inhibitors. Methods: We performed a retrospective review of patients with suspected DPP‐4 inhibitor‐associated cutaneous adverse events, at a tertiary teaching hospital from 1 January 2017 to 31 December 2020. Exclusion criteria included previous history of chronic skin disease and lack of histopathological reports or follow‐up records. The clinical characteristics, latency period, Naranjo Adverse Drug Reaction Probability Scale and clinical outcomes were evaluated. Results: In total, 18 patients (10 men, 8 women; mean age 68.6 years, range 38–89 years) were included. The DPP‐4 inhibitors used were teneligliptin (n = 6), vildagliptin (n = 6), sitagliptin (n = 4), linagliptin (n = 1) and saxagliptin (n = 1). The mean interval between therapy initiation and lesion onset was 8.8 months (range 1–24 months). The dermatoses noted were BP (n = 12; 66.6%), lichenoid dermatitis (n = 4; 22.2%), psoriasiform dermatitis (n = 1; 5.6%) and spongiotic dermatitis (n = 1; 5.6%). Eight patients (44.4%) had necrotic keratinocytes as one of the distinct histological features. Causality assessment using the Naranjo scale rated the causative role of DPP‐4 inhibitors as 'possible' in all patients. Of the 18 patients, 11 (61.1%) noted improvement in their condition following discontinuation of DPP‐4 inhibitors, with 5 having complete remission within 6 months of stopping the drug. Conclusion: DPP‐4 inhibitor‐associated dermatoses are not necessarily limited to BP. It is necessary to recognize the possibility of other dermatoses in patients on DPP‐4 inhibitors as drug substitution/cessation may improve disease morbidity. Abstract : Dipeptidyl peptidase (DPP)‐4 plays a complex role in immune regulation in various dermatological conditions and its inhibition can lead to increased risk of various dermatoses, especially bullous pemphigoid (BP). We performed a retrospective analysis of cutaneous adverse events (AEs) in patients on DPP‐4 inhibitors, finding BP to be the most common cutaneous AE, followed by lichenoid dermatitis, with other observed eruptions including psoriasiform dermatitis and spongiotic dermatitis.